Soviet Saboteurs in Lithuania (1941–1944) - Janavičienė, Audronė (Genocidas ir rezistencija, 1997)
The author’s aim is to show what the red army partisan squads and groups were like, where they operated, what their ranks were made of, and what their activities were. This is not easy. Although several collections of war documentaries and memoirs of war participants were published during the Soviet period, they are almost devoid of political or military data that is unfavourable to the regime, because they were forbidden by the NKGB agencies controlled by Moscow. Meanwhile, the authenticity of the documents that have recently been preserved and made public and the veracity of the facts are also doubtful. Only fragments of data on the topic of interest have survived in the funds of the Lithuanian Central State Archives (LCVA).
Keywords: German occupation; Soviet partisans; terror; repressions; Second World War